PENGARUH BUDAYA KERJA, PELATIHAN DAN KEPRIBADIAN TERHADAP KEPUASAN KERJA SERTA IMPLIKASINYA PADA KOMITMEN ORGANISASIONAL - Romi, Hutri Agus; Wisra, Mefri Yudi (JURNAL AKUNTANSI BARELANG, 2024)
This study is how to improve organizational commitment (Empirical Study on Security Guards of Security Service Business Entities in Batam City) partially or simultaneously work culture, training, personality and job satisfaction towards organizational commitment. The research method used is descriptive and verification involving a research sample of 373 security guards. Hypothesis testing using structural equations (Structural Equation Modeling) with the LISREL 8.70 application program. This study proves that there is a positive and significant influence of work culture, training and personality variables on job satisfaction both partially and together with a contribution of 58%. This study proves that work culture, training, personality and job satisfaction variables influence organizational commitment with a contribution of 87% with the most dominant variable influencing organizational commitment being job satisfaction. While the most dominant variable influencing job satisfaction is work culture. Another finding from the results of this study is that job satisfaction functions as a mediating variable for the three exogenous variables on organizational commitment. This study recommends improving the performance of security guards at Security Service Business Entities in Batam City by paying attention to job satisfaction, especially in rewards.